Evaluation of Surface Water Quality Based on Combined Weight-TOPSIS Mathematical Model - LIAN Haidong; MU Duo; ZHANG Shuo; XU Cundong (Renmin Zhujiang)
In order to evaluate the water worse than class V,and make a more objective and comprehensive evaluation,based on the water quality monitoring results of 8 sections in old Tongli Town,this paper divides the surface water quality standards into six classes,determines the combined weight by the combination of subjective weighting (AHP) and objective weighting (entropy weight),evaluates the water quality of old Tongli Town by the TOPSIS mathematical model improved with combined weight,and compares the results with those of other methods.The evaluation results show that:The water quality of old Tongli Town is class V or V-,and the water quality of internal section is worse than that of external section.The main impact factors for water quality are the DO and NH3-N.The combined weighting method overcomes the shortcoming of subjective weighting method or objective weighting method alone,with more scientific weighting process.The results of combined weight-TOPSIS model is basically consistent with those of the improved fuzzy comprehensive evaluation method,which can make the evaluation results more differentiated,so it is worthy of popularization and application in the evaluation of similar water quality.